Leishmaniose visceral adquirida no Estado de São Paulo (Brasil) A case of visceral leishmaniasis contracted in the State of S. Paulo, Brazil - Vicente Amato Neto; Fermin Blanco Filho (Universidade de São Paulo, 1981)
Foi descrita a notificação de um caso de leishmaniose visceral em uma criança com dois anos de idade, tendo sempre residido em Capão Redondo, localidade situada na Grande São Paulo (Brasil). Apesar de transmissão congênita ou por transfusão de sangue ter sido cogitada, é provável que a infecção tenha decorrido de mecanismo habitual, consubstanciando ocorrência autóctone relativa do Estado de São Paulo. A case of visceral leishmaniasis in a two-year-old child who has always lived in Capão Redondo, situated in Greater S. Paulo (Brazil), was reported. Although congenital transmission or blood transfusion were considered, it is probable that the infection originated in the usual mechanism, thus constituting an autochthonous occurrence in the State of S. Paulo. The State Health Department was notified of the case in order that it could be investigated and necessary measures taken.